Radiofrequency Thermal Ablation versus Bipolar Electrocautery for the Treatment of Inferior Turbinate Hypertrophy: Comparison of Efficacy and Postoperative Morbidity - Uluyol,Sinan (2016)
Introduction Numerous surgical methods are used to treat nasal obstruction due to inferior turbinate hypertrophy. The primary goal of the therapy is to maximize the nasal airway for as extended a period of time as possible while minimizing therapeutic complications. Objectives The aim of this study was to assess the effects of radiofrequency thermal ablation (RFTA) and bipolar electrocautery (BEC) on the removal of nasal obstruction in patients with inferior turbinate hypertrophy and on nasal mucociliary clearance (MCC). Patients in both groups were also evaluated in terms of postoperative morbidity. Methods We compared the outcomes of two groups of patients: those treated with RFTA (n = 23) and those who underwent BEC (n = 20). Nasal obstruction was graded using a visual analog scale (VAS) and MCC was measured using a saccharin clearance test. Both measurements were performed before and 2 months after treatment. Results Pre- and postoperative VAS scores showed significant improvement for both groups. However, MCC results did not significantly differ between two groups. Neither edema nor crust formation persisted for more than 1 week in any patients. Conclusion Submucosal cauterization with preservation of the nasal mucosa and periosteum is as effective and safe as RFTA and should be considered when planning inferior turbinate interventions.